Dance to the Two-Spirit. Mythologizations of the Queer Native - Kongerslev, Marianne (Kvinder, Køn & Forskning, 2018)
In 1998, the American anthropologist Will Roscoe referred to pre-colonial North America as “the queerest continent on the planet” (Roscoe 1998, 4), expressing a more universally accepted idea that before settlers arrived in North America, Indigenous peoples embraced and celebrated queer and trans people. Building on this anachronistic assumption, this article investigates the historical and anthropological constructions of the ‘Sacred Queer Native’ trope and argues that its attendant discourses perpetuate an idea of the ‘Sacred Queer Native’ figure as a mythological Noble Savage doomed to perish. The anthropological accounts therefore serve as settler colonial tools of elimination, relegating (queer) Indigenous peoples to the past, while emulating their ‘queerness’ in order to legitimize modern Lesbian and gay identities. At the same time, Indigenous poets celebrate(d) the same figuration as a strategy for empowerment, reclaiming historical positions of power and sovereignty through celebratory and often erotic poetries that directly and indirectly critique settler colonial heteropatriarchy. The article concludes that the contentions over the figure of the Sacred Queer Native and its anti-colonial, Indigenous counter-construction, Two-Spirit, illustrates both the constructedness of gender and sexualities and the need for continued critique in the field.